Clinical Pharmacy Technician Activities and Workforce Requirements at MOH Hospitals during Ten years Mass Gathering Hajj (2006-2015) in Makah and Al-Medina Regions, Saudi Arabia - Alomi, Yousef Ahmed; Alhennawi, Khairat; Khayayt, Nizar (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore the clinical pharmacy technician activities and workforce requirements at Ministry of Health Hospitals during mass gathering Hajj ten years (2006-2015) at Makah and Al-Medina Regions in Saudi Arabia. Methods: It is a retrospective analysis of ten years (2006-2015) of MOH hospital pharmacies during mass gathering Hajj period (15-30 days). The pharmacy technician should help the clinical pharmacist to provide pharmaceutical to all patients either Pilgrim or not Pilgrim at Makah region. It included Mona holy places hospitals; Arafat holy places hospitals, and Makah city. The workforce requirements calculated based on MOH workforce standards of hospitals. The clinical activities drive from MOH critical care services, emergency services, and mortality rate data. The nine clinical pharmacy services characterized by reduction mortality cost saving and mass gathering demand chosen. American College of Clinical Pharmacy (ACCP) model of clinical activities used. Results: The total number of Pilgrims was (1,952,817-3,161,573) with average of (2,445,208.1). The mean number of clinical pharmacy technician needed was (4.28 FTE) per each hospital at Makah. The average number of clinical pharmacy technician needed was (3.2 FTE) per hospital in Al-Medina. The central clinical pharmacy technician activities needs (1 FTE) of clinical pharmacy technician per each hospital in Makah and Al-Madina regions. The patient-centered clinical pharmacy technician services need (2 FTE) of clinical pharmacy technician per each hospital at Makah while (1 FTE) of clinical pharmacy technician per each hospital at Al-Medina region. The administrative, clinical pharmacy technician activities need (1 FTE) of clinical pharmacy technician per each hospital at Makah and Al-Madina regions. Conclusion: The clinical pharmacy technician required to assist the clinical pharmacist activities during mass gathering Hajj period. Both clinical pharmacy technician and clinical pharmacist decrease mortality and morbidity of chronic diseases during mass gathering Hajj time. They improve clinical outcome of illness and prevent the economic burden on healthcare system during mass gathering Hajj periods at MOH hospitals in Makka and Al-Madina region, Saudi Arabia.
Keywords: clinical pharmacy technician; Workload; Workforces; Mass Gathering; Hajj; Makka; Al-Madina; Ministry of Health; Saudi Arabia